Analysis of Various Driving Cycle Effected the Battery State of Charge in Regenerative Braking of Electric Vehicle - Ahmad Safarudin, Muhammad Syaqir; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2023)
The purpose of this study is to examine using Simcenter Amesim, the effect of various driving cycles on the battery state of charge (SoC) during regenerative deceleration in electric vehicles (EV). The battery SoC is a crucial parameter that impacts the overall performance and range of EVs. Regenerative braking, which converts kinetic energy into electrical energy during deceleration, plays a significant role in recharging the battery's state of charge. Simcenter Amesim, a comprehensive system simulation tool, is used to model the EV powertrain, which consists of the battery, the motor, and the regenerative braking system. Various driving cycles including urban, rural, and highway are simulated to depict a variety of driving scenarios and patterns. The simulations replicate real-world driving conditions using variables such as vehicle speed, acceleration, deceleration, and traffic conditions. The study investigates the influence of vehicle cycles on the battery SoC during regenerative braking. The simulations analyze the transfer of energy during braking events, including the energy captured and stored in the battery. The results are used to compare the battery SoC levels for various driving cycles and to evaluate the efficiency of regenerative braking in maintaining or increasing battery SoC.